Aklimasi Notochelys platynota yang akan dilepas di area target konservasi kura-kura Universitas Bengkulu - Rica Yuniar Tanjung; Aceng Ruyani (University of Bengkulu, 2019)
ABSTRACT[Acclimation Notochelys platynota That Will Be In Conservation In Area Ex Situ Bengkulu University]. The aim of this research is to know the effect of water pool in conservation target area to growth rate of N. platynota which will be released in conservation area of turtle of Bengkulu University. At the data collection stage, the pool water concentration is used P1: 100% pool water, P2: 75% pool water + 25% water well, P3: 50% pool water + 50% water well, P4: 25% pond water + 75% water Wells, P5: 100% well water. The data analyzed were weight growth rate, carapace length growth rate, growth rate of carapace width, body weight growth rate. The result is giving 100% of pool water in conservation target area of University of Bengkulu able to increas growth of N. Platynota.Keywords: Acclimation; N. platynota, Growth; Conservation Area; turtles.(Received November 19, 2018; Accepted April 15, 2019; Published June 18, 2019) ABSTRAKPenelitian ini bertujuan untuk mengetahui pengaruh pemberian air kolam di area target konservasi terhadap laju pertumbuhan N. platynota yang akan dilepas di area target konservasi kura-kura Universitas Bengkulu. Pada tahap pengumpulan data digunakan konsentrasi air kolam yaitu P1: 100 % air kolam, P2: 75% air kolam + 25% air sumur, P3: 50% air kolam + 50% air sumur, P4 : 25% air kolam + 75% air sumur, P5: 100% air sumur. Data yang dianalisis adalah laju pertumbuhan berat badan, laju pertumbuhan panjang karapaks, laju pertumbuhan lebar karapaks dan laju pertumbuhan tebal badan.. Hasil adalah pemberian 100% air kolam di area target konservasi Universitas Bengkulu mampu meningkatkan pertumbuhan N. Platynota.Kata kunci: Aklimasi; N. platynota; Pertumbuhan; Area Konservasi; kura-kura.